2014
DOI: 10.1007/s13157-014-0575-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential Vegetation Criteria for Identifying Reference-Quality Wetlands in the South-Central United States

Abstract: Reference criteria are needed for wetland monitoring and assessment programs. We used field-collected vegetation data from non-forested wetland sites in the south-central United States to establish preliminary criteria for identifying reference-quality wetlands in future surveys. Our analysis included three parts: (1) preliminary reference verification and metric ranking using boxplots and standardized effect size, (2) updating the putative reference sample and metric selection using Test Site Analysis, and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Crane (2014) similarly concluded that buffer metrics in the USA-RAM did not reliably predict vegetation diversity for Oklahoma depressional wetlands, and Bried et al (2014) showed mismatches between the USA-RAM buffer assessment and vegetation-based wetland quality classes in Oklahoma. Wetland assessment and classification in general appears to be challenging across Oklahoma due to a high degree of environmental and climatic variability (Hoagland 2000;Dvorett et al 2012Dvorett et al , 2013.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crane (2014) similarly concluded that buffer metrics in the USA-RAM did not reliably predict vegetation diversity for Oklahoma depressional wetlands, and Bried et al (2014) showed mismatches between the USA-RAM buffer assessment and vegetation-based wetland quality classes in Oklahoma. Wetland assessment and classification in general appears to be challenging across Oklahoma due to a high degree of environmental and climatic variability (Hoagland 2000;Dvorett et al 2012Dvorett et al , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…For the former, we established a 0.5-ha assessment area (usually a 40-m radius circle) in the most interior accessible part of the wetland or used the whole patch at smaller (<0.5 ha) sites. We recorded each vascular plant species rooted within or overhanging five 100-m 2 plots arranged depending on size and shape of the patch or assessment area (USEPA 2011b; Bried et al 2014). We recorded additional vascular species when observed during travel between plots or along transects in each cardinal direction to the wetland edge.…”
Section: Field Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bried et al . () extracted plant indicators of reference‐class wetlands from over 70 000 single, pair and triplet combinations of 75 candidate species, offering a shortcut around sampling entire vegetation communities in future surveys.…”
Section: Introductionmentioning
confidence: 99%
“…One of the best intensive assessment tools deployed in the MidAtlantic Region and beyond is Floristic Quality Assessment (FQA) (Bourdaghs, 2012;Bried et al, 2014;Cohen et al, 2004;Cretini et al, 2012;Lopez and Fennessy, 2002;Matthews, 2003;Mushet et al, 2002;Nichols et al, 2006). FQA uses measures of the plant community to derive an estimate of ecological condition and is based on the premise of plant species "conservatism' -a measure of each individual species' tolerance to human-mediated disturbance and its fidelity to habitat integrity (Taft et al, 1997).…”
Section: Introductionmentioning
confidence: 99%